Fatal, low renin hypertension associated with a disturbance of cortisol metabolism. Issue 12 (December 1983) - Honour, J W; Dillon, M J; Levin, M; Shah, V
Abstract : A 5 month old boy died after fever, persistently raised blood pressure, and hypokalaemia. A disorder of cortisol metabolism caused by 11 beta-hydroxysteroid dehydrogenase deficiency was detected retrospectively.